An Interval Type-2 Fuzzy Neural Network Control on Two-Axis Motion System - Ye Xiaoting; Zhang Tao; Wu Shasha (Institute of Advanced Engineering and Science, 2013)
In this paper, an interval type-2 fuzzy neural network (IT2FNN) control system is proposed to control a two-axis motion system, which is composed of two permanent magnet linear synchronous motors. The IT2FNN control system, which combines the merits of an interval type-2 fuzzy logic system and a neural network, is developed to approximate an unknown dynamic function. Moreover, adaptive learning algorithms that can train the parameters of the IT2FNN online are derived using the Lyapunov stability theorem. Furthermore, a robust compensator is proposed to confront the uncertainties. To relax the requirement for the value of the lumped uncertainty in the robust controller, an adaptive lumped uncertainty estimation law is also investigated. The proposed control algorithms are implemented. From the simulated and experimental results, the contour tracking performance of the two-axis motion control system is significantly improved and the robustness can be obtained as well using the proposed IT2FNN control system. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3528